In vitro gas production of a ration for dairy cows supplemented with isolated yeasts from apple by-products - D?az-Plascencia, D.; Rodr?guez-Muela, C.; Mancillas-Flores, P.; Corral, G.; Salvador, F.; Duran, L.; La O, Osmany (Cuban Journal of Agricultural Science, 2013)
In order to assess the effect of adding yeasts isolated from apple by-products on the in vitro gas production of a ration for dairy cows, eight inocula were developed with the strains 2, 9, 11 and 13 of Kluyveromyces lactis (Kl); 3 and 8 of Issatchenkia orientalis (Io); 4 and 6 of Saccharomyces cerevisae (Sc). The in vitro gas production technique was applied for its assessment. The eight treatments consisted of 0.2 g of complete diet + 10 mL ruminal liquid + 20 mL artificial saliva and 1 mL of inoculum of the different strains. The inocula were evaluated in 120 glass flasks of 50 mL, with three repetitions per treatment and different sampling times: 12, 24 and 48 h for the variables ammoniac nitrogen (NH3), lactic acid (LA) and yeast counting (YC). For the gas production (PG), intervals of 3, 6, 12, 24 and 48h were established. The data were assessed with the procedure Proc Mixed of SAS 9.0, for a random design of eight treatments in plots divided in time. The results showed effect (P < 0.01) of strain and fermentation time in the variables NH3, LA and YC. The lowest values of NH3 were observed with the strain Kl-2, and the highest ones with the Io-3, Io-8 and Sc-6, with values of 22.5, 24.8, 24.8 and 24.1 mM/mL, respectively. Effect (P < 0.01) was found on the YC, with best performance of the strains Kl-2, Kl-9, Kl-11, Kl-13 and Sc-6, with cell counting of 1.9, 1.3, 1.2, 1.1 and 1.0 x 107cel/mL, respectively at 48h. It is concluded that the K. lactis yeast demonstrated to be the most effctive strain for ruminal fermentation, with better performance in respect to higher cell counting and reduction of the lactic acid. Key words: yeasts, fermentation, gas production.